Enhancing Disaster Diplomacy between Indonesia and Turkey: A Study on the Roles of Non-State Actors in Collaborative Governance during the 2023 Earthquake - Siti Malaiha Dewi; Umi Qodarsasi (Universitas Muhammadiyah Yogyakarta, 2024)
Disaster diplomacy, the strategic use of humanitarian aid and disaster relief to strengthen diplomatic relations, emerged as a crucial element in international politics, particularly in the aftermath of natural disasters. This study delved into the specific case of the 2023 earthquake, focusing on the role of Indonesian non-state actors in fostering diplomatic ties through collaborative governance. Employing a descriptive qualitative methodology, the research explored the partnership between the Indonesian government and prominent non-state organizations, Muhammadiyah and Nahdlatul Ulama (NU), in executing disaster diplomacy. It revealed that Indonesia’s diplomatic relations with Turkey experienced significant enhancement due to their joint efforts in disaster management and humanitarian aid. The study identified three core elements structuring this collaborative governance: system context, driving force, and collaboration dynamics. It underscored the active involvement of Muhammadiyah and NU, analyzing how their respective disaster management centers – Muhammadiyah Disaster Management Center (MDMC) and Nahdlatul Ulama Disaster Management and Climate Change Institute (LPBINU) – played pivotal roles. Their contribution not only improved the efficiency and volume of humanitarian aid distribution but also expedited the evacuation processes. The findings contribute to understanding the complex dynamics of disaster diplomacy and the influential role of non-state actors in enhancing international relations through collaborative governance in crises.